Effect of duration of gonadotropin releasing hormone agonist on the outcome of in vitro fertilization-embryo transfer in a short-acting long regimen. Issue 1 (1st January 2019) - MU, Zhen-Ni; Sun, Zhen-Gao; Song, Jing-Yan; Liu, Hong-Gen; Qiao, Yan; Xia, Qing-Chang
ABSTRACT: Objective : To investigate the effect of the duration of gonadotropin releasing hormone agonist (GnRH-a) use on the outcome of in vitro fertilization and embryo transfer (IVF-ET) during the short-acting long-term hyperstimulation cycle. Methodology : Clinical data from 776 patients receiving controlled ovarian stimulation (COS) after short-term regimen downregulation were retrospectively analyzed. According to the duration of GnRH-a, the patients were divided into 3 groups: Group A, 14 days for GnRH-a; Group B, 15–17 days for GnRH-a; and Group C, >18 days for GnRH-a. The clinical data, treatment and clinical outcomes were compared among the groups. Results : There were no significant differences in fertilization rate, implantation rate, clinical pregnancy rate, abortion rate, ovarian hyperstimulation syndrome (OHSS) rate(P > 0.05). The total costs in group A were significantly less than those in group B and C(P < 0.001). The number of eggs and quality embryos generated in group A was significantly higher than that in groups B and C (P = 0.014, P = 0.005). Conclusions : In the short-acting GnRH agonist long protocol, satisfactory IVF-ET pregnancy outcome was obtained with the use of GnRH-a for 14 days under the premise of lowering the receptor-regulating standard. Excessive application of GnRH-a will affect the number of eggs and embryos and increase the cost of medical treatment.